Impact of Oral Contraceptive Pills on Intraocular Pressure and Central Corneal Thickness in Young Women - Saba Afzal, Ammara Affi, Muhammad Siddique, Faisal Rashid, Maria Aslam, Maryam Jabbar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To detect the impact of Oral Contraceptive Pills on Intraocular pressure and Central Corneal Thickness in young women. Methodology: A cross sectional, multi centered study was conducted on 40 young women who used oral contraceptive pills, to see the impact of famila on central corneal thickness (CCT) and intraocular pressure (IOP) in young reproductive ladies, who had the history of this drug from last 1, 3 and 6 months. Results: 40 reproductive young women participated in this study. CCT was divided into three categories 530-565µm, less than 530µm and more than 565µm. Out of these 40 women, 5 women had corneal thickness in the range of 530-565µm, 9 women had central corneal thickness less than 530µm and 23 women had central corneal thickness more than 565µm respectively. Like central corneal thickness, intraocular pressure was also divided into three categories 10-20mmHg, less than 10mmHg and more than 20mmHg. 5 women had intraocular pressure was in the range 10-20mmHg, 12 women had intraocular pressure was less than 10mmHg and 23 women have intraocular pressure was more than 20mmHg. Conclusion: Intraocular pressure and central corneal thickness was raised in ladies who had longer history of oral contraceptive pills from last 6 months. Keywords: Oral contraceptive pills, Central Corneal Thickness, Intraocular Pressure.